The Development of Comparison in Mathematics Textbook and Problem-Based Learning to Improve Mathematical Problem-Solving Ability of Junior High School Students - Purba, Azrina; Riskyka, Riskyka (Budapest International Research and Critics University, 2021)
In essence, this research is a development research with the aim of producing quality mathematics textbooks. To achieve that, the development model used in this research is the 4-D development model proposed by Thiagarajan, Semmel and Semmel (1974) which consists of the Define stage, Design stage, Develop stage and Disseminate stage. As for the quality of mathematics textbooks, the criteria proposed by Nieveen (2007) consist of Relevance, Consistency, Practically and Effectively. The subjects in this study are 7th grade students of SMP Muhammadiyah 54 Kerasaan and the object of this research Comparison in Mathematics Textbook Textbook and Problem-Based Learning. The instruments used consisted of Textbook validation sheets, student activity observation sheets, teacher ability observation sheets to manage learning, student response questionnaires and students' mathematical problem-solving ability tests. The validation results show that the textbooks are categorized as good. The results of the research trials show that: (1) the level of classical learning completeness is 76.67%; (2) the level of student activity during the learning process is in the ideal time tolerance limit criteria; (3) The level of teacher ability in managing contextual learning is good, because the average has reached the minimum criteria; (4) Student responses to the components of the device and the learning process were positive in the first and second trials; (5) The students' mathematical problem-solving ability has increased with an average score of 1.56 at the pretest and 3.07 at the post-test with an average increase (N-Gain) included in the medium category with an average of 0.512. So it can be concluded that the problem-based learning-based mathematics textbook developed meets the valid, practical and effective criteria.